206 A field trial to assess the effectiveness of setting up model outreach sti/hiv clinics for female sex workers in delhi. (24th April 2018) - Meena, Jitendra Kumar; Garg, Suneela
Abstract : Introduction: Sexually transmitted infections (STI) are associated with increased risk of HIV infection and represent a major public health problem in developing countries. The UNAIDS global guidance on HIV and sex work (2010) recommends comprehensive, accessible, acceptable, user friendly STI/HIV prevention and treatment based on local context and individual needs of female sex workers (FSWs). Methods: A field trial conducted to assess the effectiveness of specialised STI/HIV outreach clinic for FSWs. Pre and post intervention data were collected using semi-structured questionnaires (Cronbach´s a=0.74) with health counselling (safe sex, condom promotion). Data obtained on demographic characteristics, knowledge, practices, morbidity profile and clinical treatment outcomes. The study done at sentinel STI/HIV clinic near to brothels for easy accessibility. Participant's baseline assessment and management done coupled with a counselling session. Participants were followed up after 7 days and 3 months and data analysed using Mc Nemars test. Result: Out of 200 participants 156 followed up in the study. The mean age was 28.6±5.2 years and 58.2% were illiterate. 48.0% participant's reported pathological discharge suggestive of STI. On lab testing, 18 subjects were HIV seropositive and referred to ART centre. Partner management for STIs done in only 35.4% cases due to noncompliance. In pre-intervention phase majority 76.0% were aware of but only 41.0% knew transmission routes correctly. 78% had ever undergone HIV testing and only 36% used condoms regularly. Significant clinical improvement and behaviour change reported in 84.3% (p=0.003) and 82.2% (p=0.01) cases respectively. There was an improved coverage, satisfaction for STI/HIV diagnostic and management services. The coverage of condom usage and voluntary HIV testing escalated to 71.0% (p≤0.01) and 96.0% (p=0.034) respectively. Discussion: Creation of outreach clinics providing quality diagnostic and treatment aided by counselling services is an effective strategy for prevention and management of STI/HIV among high risk groups (FSWs).